In vitro Antibacterial and Cytotoxic Activities of Various Fractions of Lippia alba (Mill.) (Bangladesh Pharmaceutical Journal, 2023)
Lippia alba (Mill.) (Family: Verbenaceae) is widely known due to both ethnobotanical uses and chemical diversity. The present work was designated to determine the antimicrobial and cytotoxic activities of the aqueous ethanolic extract and various fractions of this plant. The whole plant was made into coarse powder and was extracted with 5% aqueous ethanol. The concentrated ethanolic extract (abbreviated as LAE) was successively partitioned with n-hexane (LAH), chloroform (LAC), ethyl acetate (LAA), and the remaining part was designated as water (LAQ). The antimicrobial and cytotoxic activities of extract and all these fractions were evaluated in vitro using disc diffusion technique and brine shrimp (Artemia salina) lethality assay, respectively. In antimicrobial assay, five Gram-positive and five Gram-negative bacteria and standard antibiotic ciprofloxacin (10 μg/disc) were used. All the samples were tested at four concentrations (200, 400, 600 and 800 μg/disc). Our study showed that the extractive and different fractions of L. alba had antibacterial activity against all the tested bacteria except Pseudomonas aeruginosa. Among the extractives, LAE and LAH had significant antibacterial activity when compared to standard ciprofloxacin. The zone of inhibition of LAE and LAH were found to be 14.4, 24.4, 13.4, 15.2, 18.5, 24.1, 16.1, 23.5, 23.2 and 14.5, 20.1, 12.5, 17.1, 17.5, 20.1, 12.5, 19.4, and 18.16 mm against Bacillus cereus, Staphylococcus aureus, Streptococcus-β- haemolyticus, Bacillus subtilis, Sarcina lutea, Escherichia coli, Klebsiella pneumonia, Salmonella typhi and Shigella dysenteriae, respectively, at 800 μg/disc. The median lethal concentration (LC50) in brine shrimp lethality bioassay was determined by extrapolation from graph and the values were found to be 41.9, 23.9, 21.3, 88.7, 6.7 and 7.5 μg/ml for LAQ, LAH, LAC, LAA, LAE and standard vincristine sulfate, respectively. In the study, different mortality rate was observed at different concentration and all the samples showed positive response, indicating the presence of cytotoxic components in L. alba. Phytochemical screening revealed that L. alba contains saponins, tannins, glycosides, steroids, alkaloids, terpenoids and flavonoids. The results of the study indicate that L. alba might be a good source of potent antibiotic and anticancer drugs.Bangladesh Pharmaceutical Journal 26(2): 150-156, 2023 (July)